The amazing Mrs. Pollifax [compact disc, unabridged] - Gilman, Dorothy, 1923-2012 (Recorded Books, 1989)
Mrs. Pollifax, from Brunswick, N.J., answers the call of Carstairs of the C.I.A. to act as courier and contact an agent missing in Istanbul.